Duplexing mode, ARB and modulation approaches parameters affection on LTE uplink waveform - Fatima Faydhe Al-Azzawi; Faeza Abas Abid; Zainab faydhe al-azzawi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The next generation of radio technologies designed to increase the capacity and speed of mobile networks. LTE is the first technology designed explicitly for the Next Generation Network NGN and is set to become the de-facto NGN mobile access network standard. It takes advantage of the NGN's capabilities to provide an always-on mobile data experience comparable to wired networks. In this paper LTE uplink waveforms displayed with various duplexing mode, Allocated Resources Blocks ARB, Modulation types and total information per frame, QPSK and 16 QAM used as modulation techniques and tested under AWGN and Rayleigh channels, similarity and interference of the generated waveforms tested using auto-correlation and cross-correlation respectively.